LINGUOCOGNITIVE ASPECT OF THE TRANSLATION OF SUSTAINABLE WORD COMPLEXES (BASED ON RUSSIAN AND AZERBAIJANI LANGUAGES) - Leyla Ilyas Hamidova (International Journal of Innovative Technologies in Social Science, 2020)
The article deals with one of the main and actual problems of modern translation studies - the transformation of sustainable word complexes, namely, the principles of translating SWC through the prism of the linguocognitive aspect. An attempt is made to reveal the main linguistic and translation aspects of the transformation process through the prism of the communicative function of these units in the context. Using examples that demonstrate the versatility of metaphorical thinking, the depth of the translation process is revealed, taking into account the comparison of the cognitive, cultural and pragmatic aspects of languages. By highlighting specific phenomena, each author of a work of art conceptualizes the world, filling the realities of existence with meanings, thereby constructing their own reality. The article proves that in the process of translation there is a problem of correlation of concepts presented in the USC, expressed in the relations of "content plan" and "expression plan", and related discursive possibilities for comparing these semantic categories in the translation language. Given this fact, it is possible to linguistically confirm many of the provisions concerning the content of the SWC concept. Namely, drawing a parallel between different ways of thinking, the comparison of certain concepts "spills out" the irregularities of the linguistic-cognitive worldview, that is, in order to identify these discrepancies, the article provides a conceptual analysis of options by comparing two different languages.